Infrastructure-Structural Transformation Nexus in Africa: The Role of Financial Sector Development. Journal of African Development (2021)
This study investigates the link between infrastructure and structural transformation in Africa as well as the mediating role of financial development on the nexus. We employ data from 24 African countries for the period 2003 to 2019 and adopt the system Generalized Method of Moments (sGMM) estimation technique. Our empirical results suggest that infrastructure and financial development foster structural transformation. However, our results show varying effects of ICT, electricity, and transport on sectoral value-added. Specifically, ICT infrastructure spurs the agricultural and manufacturing sectors value-added, electricity infrastructure aids all sectoral value-added, and transport infrastructure is important to the development of the manufacturing and services subsectors. Also, the agricultural and manufacturing sectors benefit more than the services sectors from financial-sector development. Overall, we find that infrastructure stimulates structural transformation. The net effect of the interaction of financial development and infrastructure on structural transformation appears to be zero, suggesting that financial development does not augment the nexus between infra- structure and structural transformation in Africa.